SALA DE RECURSOS EM SÃO BERNARDO DO CAMPO: POSSIBILIDADES E LIMITES DO APOIO EDUCACIONAL ESPECIALIZADO NA CONSTRUÇÃO DE UMA ESCOLA INCLUSIVA - Giorgi, Heloisa de Oliveira Prado (2007)
This document analyzes the possibilities and limits of the specialized educational support service in order to build an inclusive school . Currently, when it is mentioned school Inclusion, it is possible to evaluate in the theorist studies and also in the national and international laws, two differ tendencies: whole inclusion and on-going services. The specialized educational support service is included in both proposals but there are different nuances. The research has looked to establish a parallel between the concepts that basis those proposals and the specialized educational support service in the city of São Bernardo. It is about a Case Study of ethnographic kind. The research procedures adopted were the participant observation, document analyzes, forms filled and interviews with itinerant teachers invited. That Study was developed at São Bernardo do Campo municipal schools that have resources room and those teachers are habilitated in the mental deficiency special education. Those teachers work for the first four years (fundamental education) of the São Bernardo municipal schools. It was concluded that the specialized support service in São Bernardo do Campo is offered from the perspective of on-going services. In this case, the students from common classrooms, in general, are able to adapt for what have been offered, and do not require structural curricular changes. Itinerant teachers should contribute in order to help the student adaptation for what have been established. Even in this case, it is possible to consider as possibilities for those teachers, their contribution for the access and permanency of students that were historically excluded from the regular education.(AU)